2021
DOI: 10.1097/ccm.0000000000005085
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Bacterial and Viral Infection Using a Rapid Host Gene Expression Test*

Abstract: OBJECTIVES: Host gene expression signatures discriminate bacterial and viral infection but have not been translated to a clinical test platform. This study enrolled an independent cohort of patients to describe and validate a first-in-class host response bacterial/viral test. DESIGN: Subjects were recruited from 2006 to 2016. Enrollment blood samples were collected in an RNA preservative and banked for later testing. The reference standard was an expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 48 publications
1
51
0
Order By: Relevance
“…There is a growing interest in host response-based diagnostics, where most signatures focus on identifying the pathogen class (e.g., viral or bacterial) ( 55 ). Adding pathogen-specific host responses would augment the utility of such diagnostic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing interest in host response-based diagnostics, where most signatures focus on identifying the pathogen class (e.g., viral or bacterial) ( 55 ). Adding pathogen-specific host responses would augment the utility of such diagnostic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…This study is reported as per the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guideline ( S1 Checklist ). This is a secondary analysis of the RADICAL study, focusing on subjects with microbiologically confirmed bacterial ARI, viral ARI, or non-infectious illness and who had samples available to support all biomarker testing [ 23 ]. The study protocol and analysis plan for this study were not pre-specified at the time the RADICAL study was designed and implemented.…”
Section: Methodsmentioning
confidence: 99%
“…Since there is no gold standard to define whether ARI is bacterial, viral, or non-infectious, panel adjudication served as the reference standard [ 18 , 23 , 25 , 26 ]. Adjudications were performed by specialists in emergency medicine, infectious diseases, pulmonary medicine, or hospital medicine based on chart reviews performed >28 days after enrollment, and before measuring procalcitonin, the protein panel, or the mRNA panel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations